Implementation of Preexposure Prophylaxis for Human Immunodeficiency Virus Prevention Among Men Who Have Sex With Men at a New England Sexually Transmitted Diseases Clinic. Issue 11 (November 2016) - Chan, Philip A.; Glynn, Tiffany R.; Oldenburg, Catherine E.; Montgomery, Madeline C.; Robinette, Ashley E.; Almonte, Alexi; Raifman, Julia; Mena, Leandro; Patel, Rupa; Mayer, Kenneth H.; Beauchamps, Laura S.; Nunn, Amy S.
Abstract : Background: Preexposure prophylaxis (PrEP) is efficacious in preventing human immunodeficiency virus (HIV) among men who have sex with men (MSM). We assessed PrEP uptake among MSM presenting for services at a sexually transmitted diseases (STD) clinic. Methods: Men who have sex with men presenting to the Rhode Island STD Clinic between October 2013 and November 2014 were educated about, and offered, PrEP. We categorized PrEP engagement using an implementation cascade to describe gaps in uptake which described MSM who: (1) were educated about PrEP, (2) indicated interest, (3) successfully received follow-up contact, (4) scheduled an appointment, (5) attended an appointment, and (6) initiated PrEP (ie, received a prescription). Bivariate and multivariable logistic regression models were used to examine predictors of PrEP initiation. Results: A total of 234 MSM were educated about PrEP; of these, 56% expressed interest. Common reasons for lack of interest were low HIV risk perception (37%), wanting more time to consider (10%), concern about side effects (7%), and financial barriers (3%). Among those interested, 53% followed up. Of those, 51% scheduled an appointment. The most common reason patients did not schedule an appointment was low HIV risk perception (38%). Seventy-seven percent of those with an appointment attended the appointment; of those, 93% initiated PrEP. Patients with higher HIV-risk perception (adjusted odds ratios, 2.17; 95% confidence interval, 1.29–3.64) and a history of sex with an HIV-positive partner (adjusted odds ratios, 7.08; 95% confidence interval, 2.35–21.34) had significantly higher odds of initiating PrEP. Conclusions: Low HIV-risk perception was the most significant barrier to PrEP uptake among MSM attending a public STD clinic. Abstract : Low perceived human immunodeficiency virus risk was a significant barrier to preexposure prophylaxis uptake among high-risk men who have sex with men at a sexually transmitted disease clinic.